Lo psicologo psicoterapeuta: una storia giovane. Riflessioni sull’identità personale e sulla formazione - Albrizio, Maria Pia; Fabi, Marzia; Marrama, Rita; Monti, Alessandra Maria; Ponti, Massimo (Il sogno della farfalla, 2012)
The article traces the main points in the history that have contributed and contribute to forming the professional identity of a Fagiolian psychologist psychotherapist: the history of psychology and its development in Italy, its clinical profile and the legislative process which has come into being over time. History shows us that psychology has always been influenced by philosophy and medicine, and, tormented by this hiatus, it has delayed finding its own identity. The article focuses on how psychology took its footing in Italy and the strong Catholic influence is highlighted. A particularly critical view is expressed in relation to the cultural ferment present in the 60s and 70s giving rise to a request for psychology and psychotherapy that led, among other things, to the setting up of the Degree in Psychology in 1971. The Ossicini law passed on 18th February 1989, which regulates the profession by setting up a Register for Psychologists and a Register for Psychotherapists was another important step in defining the identity of the psychologist psychotherapist. A controversial aspect of the law regards the diagnosis. Does the psychological diagnosis differ from the psychiatric one? According to the authors this is the thorny question at the heart of the historic conflict between psychiatry and psychology . The last section deals with the most problematic question, highlighted by a recent ruling: psychotherapy. The article outlines the criteria of a psychotherapy whose aim is to provide a cure and attempts to deal with non-conscious thought. The medical method based on a diagnosis, prognosis and cure therefore becomes a delta into which the two main streams of clinical psychologists and medical psychiatrists flow, in a common purpose of providing treatment that aims to cure. Lastly, the authors begin to wonder whether the choice to study psychology constituted a form of rebellion to the dominant culture which, had they not come across the Collective Analysis group, would have proven to be a failure.